Music policy into practice: ethnographic perspectives on local music service provisions in England - Horner, Kristen Jade (2024)
The National Plan for Music Education (NPME, 2011) was the first nationwide policy paper for music in English schools. Its impacts were two-fold. Firstly, it sought to unify the work of music education providers in a historically “fragmented and uncoordinated" field through the establishment of Music Education Hubs (MEHs; Henley, 2011, pg. 30). Secondly, the Plan introduced Whole Class Ensemble Teaching (WCET) as a national entitlement to all children and young people.